Investigation on parameters influence first flush occurrence in urban residential catchment - Alias, N. (2015)
The knowledge of first flush is important particularly when dealing with stormwater treatment plant. Therefore, the parameters influence the first flush occurrence is essential. The objective of this study was to identify the influence of rainfall characteristics, catchment characteristics and type of pollutants on first flush occurrence. The study was conducted in an urban residential. 23 storm events were sampled and analysed for three water quality parameters; total suspended solids, total phosphorus and total nitrogen. Results show that the existence of first flush is depends on the rainfall characteristics, catchment characteristics and type of pollutant.